Transferências voluntárias da união em tempos de crise: o caso da Universidade Estadual da Paraíba - Neto, Manoel Morais da Silva (2018)
The present study sought to investigate the transfers of Union resources for the State University of Paraíba (UEPB), in the 2012-2017 period. Seeking to ensure the effectiveness of their public policies the Federal Government adopted as from 1988 with your citizen Constitution, decentralization of resources and included in your budget resources to social programs of its organs to It is transferred to the other Federation ones through voluntary transfers, that can be classified as covenants, terms of cooperation or transfer agreements. Through the publication of notices of these programs, interested managers may refer to the analysis of the budget authority, projects whose ultimate goal is aligned with the purpose of each program. So that these projects are concluded and, in fact, become covenants, it is necessary that several requirements are respected. Knowing that education is one of the strategic areas of the society and that's UEPB one of the main institutions of higher education in the State of Paraíba and in the Northeast region, emerged the need to investigate and detail in descriptive form the impact of the economic crisis faced by the country from 2015 on the TVUs for this institution. From the methodological point of view, to the achievement of its objectives, the study performed a documentary and descriptive research. As a main result found is the negative impact of the economic crisis of the period on scenario of TVUs, budget cuts, decrease in resources transferred and even shrinkage of fundamental assistance programs, factors that influenced negatively the transfers of these features to the UEPB, despite the tendency of recovery from 2016, in line with the economic recovery period.